2020
DOI: 10.1111/and.13879
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements in the management of varicocele‐induced infertility: A review of potential mechanisms

Abstract: Varicocele is a main cause of lower production of spermatozoon and infertility with multiple pathophysiological mechanisms. In the past decades, the use of dietary supplements has significantly increased due to both the modern lifestyle and the food shortages of the industrialised countries. The purpose of this review paper is to collect scientific evidences from basic and clinical studies which support the use of dietary supplements to define the clinical framework for patients with varicocele. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 149 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…The high content of PUFAs in the sperm plasma membrane, makes them susceptible to lipid peroxidation in presence of oxidative stress (OS) [ 13 ]. Male infertility may be due to an inflammation-mediated OS including varicocele, tobacco usage, alcohol, obesity/metabolic syndrome, leukocytospermia, sexually transmitted disease, bacterial prostatitis, and viral infections [ 14 , 15 , 16 , 17 ]. Inflammation status may be associated also with idiopathic infertility [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high content of PUFAs in the sperm plasma membrane, makes them susceptible to lipid peroxidation in presence of oxidative stress (OS) [ 13 ]. Male infertility may be due to an inflammation-mediated OS including varicocele, tobacco usage, alcohol, obesity/metabolic syndrome, leukocytospermia, sexually transmitted disease, bacterial prostatitis, and viral infections [ 14 , 15 , 16 , 17 ]. Inflammation status may be associated also with idiopathic infertility [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathophysiological mechanisms of male infertility caused by VC have not been elucidated, current studies have focused on elevated local testicular temperature, oxidative stress, metabolite accumulation, and hormonal disorders (Razi et al, 2021). Varicocelectomy, the primary treatment for varicoceleassociated male infertility, can mitigate delayed testicular development and impaired semen quality, but studies have shown that some patients still do not return to baseline semen quality after surgery (Arab et al, 2021;Shomarufov et al, 2022). There is an urgent need to find effective complementary alternative therapies.…”
Section: Introductionmentioning
confidence: 99%